Becoming Sacred. The Use of the Body in Identity Transformation - Šantek, Goran Pavel (Array, 2007)
This paper will analyze various ways of using of the human body and senses in religious practice of the Catholic movement Neocatechumenal Way. This religious movement, established in Spain in 1960s, especially emphasizes ritual practice, which is considered to be the main instrument of communication with the sacred other. Innovations in ritual practice and their symbolic interpretations are followed by careful planning how to achieve full engagement, contemplative as well as bodily and sensory, of the members in ritual acts. The aim of the paper is to make a contribution, based on new fieldwork data, to the research of bodily and sensory dimensions of ritual practice.